EFFECT OF SIMULATED APPOINTMENT SCHEDULES ON THE OPERATIONAL PERFORMANCE OF A UNIVERSITY MEDICAL CLINIC - Vijayan, Arunn Pisharody; Pusapati , Vamsi K V; Prabhakar , Nandakumar; Aghazadeh, Fereydoun (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
High patient wait times, physician idle times, physician overtimes, and patient congestion are common problems encountered in clinics that add to health care costs. This paper investigates the effect of different appointment systems on the operational performance of a university clinic. The process at a student health center was modeled using the Rockwell Arena® simulation software. Individual Block rule, Bailey rule, 3-Bailey rule, and the Two-at-a-time rule were compared using the simulation model to test their effect on performance parameters. The performance parameters were the provider measures and patient measures. The individual block rule was the most patient-friendly with the shortest patient measures. The 3-Bailey rule was the most provider-friendly rule, which resulted in the least provider times. A Kepner-Tregoe analysis shows that the Bailey rule was the most suitable as it had a good trade-off between the patient and provider times compared to the others.